(untitled) (Research, Society and Development, 2022)
As a health professional, biomedical practitioners must have knowledge about the concept and strategies of health promotion to act with such guidance, through the exercise of practices and forms of dialogue with society, improving these strategies according to the current context. In this sense, the study aims to analyze what the literature presents about the relationship between the biomedical professional and health promotion. This is a scope review that had the following guiding question: How is the Brazilian scientific production on biomedical professionals and health promotion characterized in national journals since 1999? Even though a portion of the articles found focus on the role of the biomedic, as identified in the analysis, all indicate weaknesses and effects arising from academic training. Thus, it was indicated that greater integration between courses in the health area, practical experience with application to society, studies with an anthropological perspective and an emphasis on interdisciplinarity would help in a broader training for the exercise of the biomedical professional in health promotion.